Education and joy: Affects in the construction of a possible dialogue between Espinosa y Snyders - Luis Saldanha Da Silva, Valmir; Henrique Joaquim, Pedro (Revista Colombiana de Ciencias Sociales, 2026)
This article is the result of a theoretical and qualitative investigation, based on a conceptual bibliographic survey. In it, the objective was to rescue Spinoza’s dynamics of affections and bring it closer to the relational dimension in educational processes, giving relevance to affections in pedagogical environments. It also draws a dialogue between the Spinozist tradition of thought and the philosophy of education based on joy, a topic debated by Georges Snyders. The conclusion points to the need to revalidate the aesthetic paradigm as a pedagogical vector in which it is possible to conceive affections, joys, and affects, relate them to the development of the sensitive, and take them as the basis of an emancipatory pedagogical praxis.